The Effect of Classroom Composition and Size on Learning Outcomes for Italian and Immigrant Students in High School - Elisa Cavicchiolo; Fabio Alivernini (LED Edizioni Universitarie, 2018)
Students cannot change the composition and the size of the classroom they attend, and the effect of these variables on achievement is a source of educational inequality. In this study, based on a representative sample of Italian high school students (N = 26,799), a multilevel analysis was performed to: (i) estimate the overall impact of the structural characteristics of the class on achievements; (ii) identify which of the analysed characteristics were more relevant. The results show that the structure of the classroom has a significant impact on academic performance, and they identify group's initial learning level and gender composition as the most important factors. The overall socio- economic level of the class and the percentage of immigrant students proved to have a lower impact, which varied according to different geographical areas, and the group size does not seem to be relevant. In conclusion, if the outcome of interest is academic performance, results suggest that the classroom size and the number of immigrant students attending the class has little or no relevance in high school, while the group's initial achievement, the gender composition and, to a lesser extent, the socio-economic composition of the group should be taken into consideration. Given the complexity of the objectives of the  educational system in Italy, which are by no means limited to the improvement of academic results, future studies will have to examine the effects of the structure of the classroom also on noncognitive outcomes that are closely related to students' personal and social development.